Pengaruh Kualitas Produk, Kualitas Pelayanan, Dan Persepsi Harga Terhadap Keputusan Pembelian Pada Depot Air Pray Gondrong Jakarta - Abdillah Dattul Kahfie; Suadi Sapta Putra; Kumba Digdowiseiso (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine the effect of product quality, service quality and price perceptions on purchasing decisions for Air Pray Gondrong Jakarta. The population in this study used a purposive sampling technique where the population taken was 100 people with a significance level of 95% and a standard deviation of 25%. This study uses primary data with data collection methods through questionnaires distributed to 100 respondents. The data analysis technique uses inferential analysis with multiple linear regression and uses the Statistical Product and Service Solution (SPSS) version 26.0 program. The results showed that product quality had a positive and significant effect on purchasing decisions with a path coefficient value of 0.269 and a significant t of 0.005. Service quality has a positive and significant effect on purchasing decisions with a path coefficient value of 0.178 and a significant t of 0.033. Price perception has a positive and significant effect on purchasing decisions with a path coefficient value of 0.400 and a significant t of 0.000. Keywords: Product quality, Services Quality, Price perceprtions, Purchasing decisions